Mapping the Values Landscape: Understanding the Strategic Role of Core Values in Organizational Success (Journal of Informatics Education and Research, 2025)
This research delves into the organizational values of fourteen distinct organizations by utilizing student data gathered on their interpretation of ten fundamental values. The purpose of the study is to determine how these fundamental principles affect performance and organization and how they are ranked differently. Understanding the organizational culture and decision-making procedures needs this examination. The study intends to enhance understanding of organizational priorities and their likely effects on stakeholder relationships, organizational success, and employee happiness by emphasizing the significance of values.